Serum Lipid Profiles and All-Cause Mortality: A Retrospective Single Center Study on Chinese Inpatient Centenarians - Zou, Xiao; Li, Jian-hua; Hu, Yi-xin; Wang, Hai-jun; Sun, Sha-sha; Xu, Wei-hao; Deng, Xin-li; Sun, Ting; Cao, Jian; Fan, Li; Si, Quan-jin (Frontiers in Public Health, 2022)
Objectives To analyze the serum lipid profiles and investigate the relationship between the lipoprotein cholesterol levels and all-cause mortality in the Chinese inpatient centenarians. Design Retrospective study. Methods Patients over 100 years old in our hospital with available clinical data were enrolled. There were totally 121 centenarians were receiving a follow-up till to April 2021 of all-cause mortality and serum lipid profiles, including total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) levels. Cox proportional hazard models were used to assess the association between the lipoprotein cholesterol and all-cause mortality. Results 1)The average age of the 121 centenarians were 100.85±1.37 years old (100 107 years), including 114 males and 7 females. 2) The rate of treatment with lipid-lowering drugs was 69.4%, and the lipid-lowering drugs were mainly statins (63.6%). 3) The serum lipid status were as following: TC 3.90±0.69mmol/L, TG 1.36±0.55mmol/L, HDL-C 1.14±0.24mmol/L, and LDL-C 2.05±0.46mmol/L. 4) During a 589-day (95%CI: 475, 703) follow-up, there were 80 deaths among the 121 centenarians. The all-cause mortality rate was 66.1%. Multivariable analysis showed that higher TC level (HR=2.071, 95%CI=1.275-3.363, P=0.003), lower LDL-C level (HR=0.406, 95%CI=0.231-0.713, P=0.002), and lower HDL-C level (HR=0.231, 95%CI=0.059-0.898, P=0.034) were independent factors contributed to the all-cause mortality. Conclusions The serum lipid profiles of the Chinese inpatient centenarians were lower than previous studies. Low LDL-C level was associated with an increased risk of all-cause mortality, which may indicate that quite low level of LDL-C had a potential harmful effect on the all-cause mortality for the centenarians.